Improved actuated strain of dielectric elastomer through disruption of hydrogen bonds of thermoplastic polyurethane by adding diaminonaphthalene. (20th February 2015) - Ning, Nanying; Yan, Bingyue; Liu, Suting; Yao, Yang; Zhang, Liqun; Chan, Tung W; Nishi, Toshio; Tian, Ming
Abstract: We used a novel and simple approach to increase the actuated strain at low electric field of thermoplastic polyurethane (TPU) through the disruption of the hydrogen bonds of TPU by adding diaminonaphthalene (DAN) into the matrix. DAN as proton donors disrupted the original N–H/C=O hydrogen bonds between the TPU chains, improving the polarizability of the chains, thus increasing the dielectric constant of TPU. Meanwhile, DAN greatly decreased the elastic modulus of TPU by disrupting the hydrogen bonds of TPU. The simultaneous increase in dielectric constant and decrease in elastic modulus resulted in a 330% increase in electromechanical sensitivity at 10 3 Hz and a 500% increase in actuated strain at the low electric field of 20 V μ m −1, facilitating the application of dielectric elastomers (DEs) in the biological and medical fields, where a low electric field is required. In addition, our DAN/TPU DE exhibited good mechanical strength.